Discharge Planning on Postpartum Who has Low Birth Weight (LBW) Babies with The Practice of LBW Babies Care at Home - Ditha Rizky Oktavianti; Sri Rahayu; Listyaning Eko Martanti (JURNAL KEBIDANAN, 2020)
Mother have an important role in caring for and nurturing their babies well. It is necessary to provide education to mother and family through discharge planning. Discharge planning is a process that aims to help patients and families in improving or maintaining their health status. The purpose of this research is to know the effect of discharge planning on postpartum mother who has LBW babies against the practice of LBW babies care at home after treatment in dr. Doris Sylvanus hospital. Type of research was quasi-experimental (Pretest-Posttest with control group design). The population is the postpartum who has LBW baby. Sampling using Purpose Sampling technique with treatment group of 16 respondents was given discharge planning with module and 16 respondents were given health education with leaflet. The practice of treating LBW baby at home is assessed after the baby comes home with a checklist. Data analyzed using paired samples t-test and independent samples t-test. The results were dominated by the age group of 20-35 years old, most of them have the level of secondary education and work as housewife. There was an effect of discharge planning on postpartum mother to the practice of infant care LBW with p-value 0.0001. There was an increase of the mean for the control group (3.05) and the treatment group (9.45). The involvement of mothers in care when the baby is still in the hospital and the hospital can give discharge planning about baby care at home before baby LBW is allowed home.